Successful treatment with the mTOR inhibitor everolimus in a patient with Perivascular epithelioid cell tumor - Gennatas, Constantine (BioMed Central, 2012)
Perivascular epithelioid cell tumor (PEComa) is an extremely rare neoplasm that appears to arise most commonly at visceral (especially gastrointestinal and uterine), retroperitoneal, and abdominopelvic sites. Malignant PEComas exist but are very rare. These tumors represent a family of mesenchymal neoplasms, mechanistically linked through activation of the mTOR signaling pathway. Metastatic PEComa is a rare form of sarcoma for which no effective therapy has been described previously and that has a uniformly fatal outcome. Although there is no known effective therapy, the molecular pathophysiology of aberrant mTOR signaling provides a scientific rationale to target this pathway therapeutically. The difficulty in determining optimal therapy, owing to the sparse literature available, led us to present this case. On this basis, we report a case of metastatic retroperitoneal PEComa treated with an oral mTOR inhibitor, with everolimus achieving significant clinical response.